First record of Ledenbergia macrantha Standley (Phytolaccaceae) in the state of Veracruz, Mexico - Olivia Rivera, Hector; Ramon Farias, Feliza (Instituto de Ecología, A.C., 1992)
Ledenbergia macrantha Standley (Phytolaccaceae) is reported for the first time for the flora of the state of Veracruz, in the municipality of Amatlan de los Reyes; some additional data on its distribution in the country are included.